Sternectomy for Treating Advanced Non-Melanoma Skin Cancer. (30th May 2019) - Pinheiro, Victor Emmanuel Gadelha; Bezerra, Bianca Rohsner; Farias, Luís Arthur Brasil Gadelha; Araujo Filho, Irapuan Teles de; da Fonseca, Marcio Ribeiro Studart
Abstract : Introduction . Skin cancer is a rare indication of sternectomy. Our goal is to report the clinical course of seven patients who underwent sternectomy for skin cancer. Methods . The survey data were collected from medical records of patients treated between 2008 and 2018 at Ceará Cancer Institute. Results . All patients had prolonged sunlight exposure and average disease time of two years and age of 60 years. Most patients recovered favorably after treatment with prolonged survival. Conclusion . Sternectomy remains an option with curative purposes for locally advanced skin cancer.